A comparison of the NZDep and New Zealand IMD indexes of socioeconomic deprivation. (2nd January 2020) - Crampton, Peter; Salmond, Clare; Atkinson, June
ABSTRACT: The aims of this study were to compare the NZ Indices of Multiple Deprivation (IMD) with the NZDep index of socioeconomic deprivation in terms of their: (1) theoretical and methodological approaches; (2) use of small areas; (3) rankings of small areas; and (4) relationships with various health and social outcomes. Literature sources were reviewed for aim 1. The data sources for aims 2–4, all contained within Statistics New Zealand's Integrated Data Infrastructure, were: (1) 2013 Census, (2) health data sets, (3) Police database, and (4) 2014 General Social Survey. Outcomes were smoking, mortality, respiratory disease, crime, self-assessed health status. Spearman's rho was used as a measure of correlation. Deciles were treated as categorical in the stepwise logistic regressions. The key finding is that there is a range of theoretical and methodological differences between the indexes. Despite these differences, the indexes behave in a similar, but not identical, manner in their ranking of small areas and in their associations with health and social outcomes. In conclusion, for practical purposes for many applications the two indexes give similar results when analysing very large data sets, although there are some important caveats related to this conclusion for both large and small data sets.